Tagalog journalism in Renacimiento Filipino (1910-1913) sowing the seeds of the nationalist essay in Philippine Literature - Guieb, Eulalio R., III (2013)
Tagalog journalism in the publication Renacimiento Filipino (1910-1913) can be deemed as one of the initial sowing of seeds of nationalist essay in Philippine literature. The twenty-eight essays by Francisco Laksamana, Faustino Aguilar, Carlos Ronquillo, Precioso Palma, Julian C. Balmaseda, Iñigo Ed. Regalado, Dionisio S. Agustin and others examined for this study embodied the Filipinos' sentiments on tearing down the bastion of dubious knowledge installed by both the outgoing Spanish colonizers and the intruding Americans. This study identifies four views that were criticized by the essays in Renacimiento Filipino. The first pertains to things or events that were purportedly prescribed by God. The second is supposed natural state of inequality among the people. The third is the alleged inherent indolence of the Filipinos which is one of the reasons for the people's poverty. The fourth is the Filipinos' acceptance of the united States as the Savior of the Philippines.